Efektivitas Pemberian Air Rebusan Daun Sirsak (Anonna Muricata) terhadap Penurunan Kadar Asam Urat pada Lansia di Kelurahan Rambung Timur Kecamatan Binjai Selatan 2025 - Hanna Ester Empraninta; Piyanti Saurina Mahdalena Sagala; Sembiring Ananta Sherina (Pusat riset dan Inovasi Nasional, 2025)
Gout is a disease that is often found in the world. Usually gout occurs due to the deposition of monosidium urate crystals in the tissue or due to supersaturation of uric acid in the extracellular fluid. Some factors that cause gout include excessive purine intake. An unhealthy diet and high-protein foods with high purine levels. One of the non-pharmacological actions in reducing uric acid levels is the provision of soursop leaf decoction (Annona Muricata L) intervention. To determine the effectiveness of soursop leaf decoction on reducing uric acid levels in the elderly by administering soursop leaf decoction in Rambung Village, South Binjai District, Binjai City. This study uses a One-group pretest-posttest design research design approach. The sample of this study was 8 respondents. The sampling technique uses total sampling. The collection of research data uses demographic data, a consent sheet to become a respondent (Informed Consent). Data collection is carried out through observations by researchers of respondents and conducting observations. Research with Parametric Test Paired Sample T-test obtained a p Value of (0.000) <α (0.05), so there is a significant effectiveness of giving soursop leaf decoction to reduce uric acid levels in the elderly, and can be used as an alternative to reduce uric acid levels.